ANALYSIS THE USE OF BORE PILE FOUNDATION ON ALLUVIAL SAND AND TUFFACEOUS SANDSTONES AT MARGATIGA DAM PROJECT - Wahyu Prakoso; Nugraha Nugraha; Reyzansza Anandio Syahputra; Stella Monica (JURNAL TEKNIK HIDRAULIK, 2022)
The elevation of the dam building foundation plan is at an elevation of +06.00 and +08.00, the results of sub-surface tests including the Standard Penetration Test (SPT) and Pressure Meter Test (PMT) show that at these elevations the SPT value is < 20 or categorized as loose rock and the PMT results shows a lateral pressure of <3 – 10 MPa or categorized as very soft rock - soft rock. The results of the sub-surface test show that the type of rock constituent in the dam building consists of layers of alluvial sand and tuffaceous sandstone. Based on the technical specifications, the foundation must be at SPT value > 50 or in very dense rock layer, if the dam building foundation is still built at the elevation of the foundation plan, it can cause the building to become unstable due to the rock layer at that elevation not able to support the weight of the building. SPT values >50 was found at an elevation of +01.00 - -02.00 or 7 to 10 meters from the design elevation of the foundation. Furthermore, an analysis is carried out based on the results of sub-surface test to determine the method of strengthen the foundation. The results of the analysis show that the bore pile foundation is effective as a method of foundation strengthen. The analysis includes the analysis of the ultimate bearing capacity, the axial allowance bearing capacity of the pile foundation and the bearing capacity of the pile group foundation. Based on the analysis, strengthening the foundation of intake area requires 156 piles with a depth of 19 meters, the spillway area requires 196 piles with a depth of 17 meters and the retaining wall area requires 64 piles with a depth of 15 meters. Keywords:             Sub-surface test; alluvial sand; tuffaceous sandstone; bore pile; bearing capacity